2020
DOI: 10.1111/hel.12742
|View full text |Cite
|
Sign up to set email alerts
|

Review: Helicobacter pylori infection in children

Abstract: Helicobacter pylori infection in children and adolescents differs in comparison to adults with respect to epidemiology, host responses, and disease manifestations. Furthermore, treatment options are limited in this population and antibiotic resistance rates continue to increase. Therefore, ongoing research is vital to understand disease pathogenesis and provide optimal management of children with infection. This review summarizes relevant publications from April 2019 to March 2020. Similar to adults, recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Although most H. pylori -infected children do not have obvious clinical symptoms, studies have shown that children with gastrointestinal symptoms have a higher rate of H. pylori infection, and the infection rates are affected by socioeconomic status, living habit, sanitary conditions, geographic region, etc. [ 4 , 5 ]. Despite the overall infection rate has slowly declined in China, the infection rate in rural areas is still much higher over that of city residents[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most H. pylori -infected children do not have obvious clinical symptoms, studies have shown that children with gastrointestinal symptoms have a higher rate of H. pylori infection, and the infection rates are affected by socioeconomic status, living habit, sanitary conditions, geographic region, etc. [ 4 , 5 ]. Despite the overall infection rate has slowly declined in China, the infection rate in rural areas is still much higher over that of city residents[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that up to 70% of the world’s population carries this bacterium, especially in developing countries [ 2 , 9 , 10 ]. H. pylori infection usually occurs in childhood, and when untreated, remains present in the life of the host [ 3 , 6 , 11 ]. The infection is usually associated with asymptomatic gastritis, and in the long-term it may result in more severe clinical outcomes, such as gastric ulcer, duodenal ulcer, and gastric cancer [ 2 , 3 , 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reports huge regional differences among with more than half of the world's population infected 1 . East Asia, particularly Japan, South Korea and China, and western Europe have higher rates of gastric cancer as compared to other regions 2–4 . In China, the annual prevalence and mortality due to gastric cancer are more than twice the global average 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 East Asia, particularly Japan, South Korea and China, and western Europe have higher rates of gastric cancer as compared to other regions. 2 , 3 , 4 In China, the annual prevalence and mortality due to gastric cancer are more than twice the global average. 5 , 6 , 7 In China, annually, there are 679,100 new cases and 498,000 gastric cancer‐associated deaths; these account for 23% of all deaths from malignant tumors.…”
Section: Introductionmentioning
confidence: 99%